A Case Study of The Performance of Muslim MSMEs in Purwokerto City - Fatmah Bagis (ITB AAS INDONESIA Surakarta, 2021)
This research is a case study of the performance of Muslim MSME employees in Purwokerto City with variables that affect job satisfaction, organizational culture and work environment. Respondents used were Muslim MSME employees in South Purwokerto District as many as 142 Muslim employees. The analysis technique uses PLS (Partial Least Square). Research shows that job satisfaction, organizational culture and work environment affect the performance of Muslim MSME employees in South Purwokerto District. The results show that job satisfaction has no effect on employee performance. Meanwhile, organizational culture and work environment affect employee performance Keywords : MSME employee performance, job satisfaction, organizational culture, work environment